Social networks, mobility, and political participation: The potential for women’s self-help groups to improve access and use of public entitlement schemes in India - Kumar, Neha; Raghunathan, Kalyani; Arrieta, Alejandra; Jilani, Amir Hamza; Chakrabarti, Suman; Menon, Purnima; Quisumbing, Agnes R. (International Food Policy Research Institute, 2018)
Women’s self-help groups (SHGs) have increasingly been used as a vehicle for social, political, and economic empowerment as well as a platform for service delivery. Although a growing body of literature shows evidence of positive impacts of SHGs on various measures of empowerment, our understanding of ways in which SHGs improve awareness and use of public services is limited. To fill this knowledge gap, this paper first examines how SHG membership is associated with political participation, awareness, and use of government entitlement schemes. It further examines the effect of SHG membership on various measures of social networks and mobility. Using data collected in 2015 across five Indian states and matching methods to correct for endogeneity of SHG membership, we find that SHG members are more politically engaged. We also find that SHG members are not only more likely to know of certain public entitlements than non-members, they are significantly more likely to avail of a greater number of public entitlement schemes. Additionally, SHG members have wider social networks and greater mobility as compared to non-members. Our results suggest that SHGs have the potential to increase their members’ ability to hold public entities accountable and demand what is rightfully theirs. An important insight, however, is that the SHGs themselves cannot be expected to increase knowledge of public entitlement schemes in absence of a deliberate effort to do so by an external agency.